2019
DOI: 10.1002/anie.201911252
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Multicompartmental Particles Using 3D Microfluidics

Abstract: A microfluidic assembly method based on a microfluidic chip and capillary device was developed to create multicompartmental particles. The microfluidic chip design endows the particles with regulable internal structure. By adjusting the microstructure of the chip, the diameter of the capillary, the gap length between the two microfluidic components, and the flow rates, the size of the particles and the number or the ratio of different regions within the particle could be widely varied. As a proof of concept, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 25 publications
0
44
0
Order By: Relevance
“…Wu et al. [ 48 ] developed a microfluidic assembly technology based on a microfluidic chip and a capillary device, which was used to manipulate the microfluidics ingeniously and could be used to create multicompartment microspheres. As convincing evidence, they found some complex microspheres that contained 20 small compartments, which has never been reported before.…”
Section: Devices For and Fabrication Of Microfluidic Hydrogel Microspheresmentioning
confidence: 99%
“…Wu et al. [ 48 ] developed a microfluidic assembly technology based on a microfluidic chip and a capillary device, which was used to manipulate the microfluidics ingeniously and could be used to create multicompartment microspheres. As convincing evidence, they found some complex microspheres that contained 20 small compartments, which has never been reported before.…”
Section: Devices For and Fabrication Of Microfluidic Hydrogel Microspheresmentioning
confidence: 99%
“…Recently, Lin et al suggested microparticles with ten-, even twenty-compartment by utilizing a vertical integrated chip-capillary droplet generator. 163 Benefitting from the superior compartment structure, this microparticle was found to have high compatibility, enabling different kinds of cells encapsulated to exhibit high viability during culturing (Figure 16B). In addition, Janus microparticles, which possess different physicochemical functionalities on the two hemispheres, provide a projecting platform for cell co-culture.…”
Section: Cell Culturementioning
confidence: 99%
“…However, it is still a challenge to solve the problem of drug loading rate of hydrophilic drugs and adverse reactions caused by sudden release. Multi-compartment particles allow multiple materials to be used in different separation phases, thus creating two or more compartments, allowing individual particle to have different characteristics, such as independent release when encapsulating drugs, and also encapsulate magnetic beads, photosensitizers and nucleic acids [73][74][75][76]. At present, due to the limitation of the preparation process, the preparation of double compartments is relatively easy to realize, but it is not so easy to obtain more stable multi-compartment micro/ nanoparticle.…”
Section: Types Of Plga Micro/nanoparticlementioning
confidence: 99%